2017
DOI: 10.1002/cbin.10872
|View full text |Cite
|
Sign up to set email alerts
|

Collagen peptides modulate the metabolism of extracellular matrix by human dermal fibroblasts derived from sun‐protected and sun‐exposed body sites

Abstract: Clinical data published in recent years have demonstrated positive effects of collagen hydrolysate (CH) on skin aging clinical signs. CH use as food supplement has a long history; however, few studies have addressed the underlying purpose of CH on the cellular and molecular biology of skin cells that could elucidate clinical improvement findings. Wide diversity of characteristics has been reported for dermal fibroblasts derived from different body sites and it is unknown whether collagen peptides could modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In 2018, Zague et al reported that collagen peptides modulate the metabolism of extracellular matrix proteins by human dermal fibroblasts (in culture) that were derived from sun-protected and sun-exposed body sites [ 23 ]. The in vitro collagen hydrolysate treatment increased the dermal matrix precursors along with procollagen type I and collagen type I proteins.…”
Section: Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Zague et al reported that collagen peptides modulate the metabolism of extracellular matrix proteins by human dermal fibroblasts (in culture) that were derived from sun-protected and sun-exposed body sites [ 23 ]. The in vitro collagen hydrolysate treatment increased the dermal matrix precursors along with procollagen type I and collagen type I proteins.…”
Section: Collagenmentioning
confidence: 99%
“…The in vitro collagen hydrolysate treatment increased the dermal matrix precursors along with procollagen type I and collagen type I proteins. The increased levels of collagen were attributed to enhanced biosynthesis of collagens by fibroblasts but also decreased collagen type I metabolism through the inhibition of metalloproteinases (MMP 1 and MMP 2) activities [ 23 ]. The authors concluded that food-derived collagen hydrolysates improved skin cells and dermal health by enhancing collagen production and inhibiting the enzymes that break it down.…”
Section: Collagenmentioning
confidence: 99%
“…While in our previous study there were no significant effects on dermal density determined after 12 weeks of supplementation with CoQ10 alone, by the addition of collagen peptides and other nutrients to the test product, significant improvement in dermal density (16.1%) in comparison to the placebo was achieved in the present study, while dermis thickness was not affected. As dermis density is related to the amount of properly structured dermal proteins, e.g., collagen and elastin, the test product may have reduced degradation or promoted the synthesis of structural proteins as shown for collagen peptides in some in vivo [15], animal [45] and in vitro [46] studies as well in some in vitro studies for CoQ10 [39,42,43]. The observed improvement in dermal density is almost double when compared to the previously reported influence of supplementation, with a 2.5-fold dose of CP alone (10 g/day; 8.8% improvement) [17], indicating that some synergy may develop when using CoQ10 and CP simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Culture flasks were incubated at 37 C in a humidified atmosphere of 5% CO 2 . The second to third passages of fibroblasts were used for the experiment [34].…”
Section: Isolation Of Primary Nasal Fibroblastsmentioning
confidence: 99%